Study of the effects of promoters (MnOx and FeOx) on Co3O4/CeO2 during Preferential Oxidation of Carbon monoxide - Ndila, Noluvuyo (Department of Chemical Engineering, 2023)
The provision of sustainable, clean, safe, reliable, and affordable energy towards the advancement of the quality of life in all societies is goal 7 of the United Nations sustainable development goals . Currently, most energy production relies on the use of fossil fuels (Büyüközkan, Karabulut and Mukul, 2018). However, these have negative environmental impacts such as global warming, land degradation, and water pollution (Haryanto et al., 2005). Hence there is an urgent need for improving access to eco-friendly and reliable energy alternatives. One of the leading and promising pollution-free high-energy carriers is hydrogen for fuel cells. Currently, hydrogen gas is mostly produced via steam reforming followed by the water-gas shift reaction (Edwards et al., 2008). However, the concern with using this hydrogen in fuel cells is the carbon monoxide content which is between 0.5-1.0 vol % (Liu, Song & Subramani, 2010). Carbon monoxide is poisonous to the platinum anode of the fuel cell so it needs to be reduced to below 10 ppm before being introduced in the fuel cell (Liu, Song & Subramani, 2010). One of the methods for carbon monoxide removal is preferential oxidation (PROX) of carbon monoxide to carbon dioxide. This process has been identified as being cost-effective, much easier to implement, and ensures minimum loss of hydrogen when compared to other techniques such as selective CO methanation and pressure swing adsorption (Park, Lee and Lee, 2009). Catalysts used for CO-PROX are either noble metal or transition metal oxide based. Noble metal-based catalysts have a low CO oxidation activity at temperatures below 200 °C, higher cost, and lower availability when compared to transition metal-based catalysts (Kahlich, Gasteiger & Behm, 1997; Grisel et al., 2002). Of the transition metal oxides, Co3O4 and CuO are the most active catalysts for CO-PROX (Woods et al., 2010). The active species for CO oxidation in Co3O4 catalysts is the Co3+/Co2+ redox pair. However, during CO-PROX at temperatures above 200 °C, Co3O4 reduces to metallic Co which is active for CO methanation (Nyathi, 2016; Khasu, 2017). This is undesirable as CO methanation results in H2 consumption, hence the stability of the Co3O4 phase above 200 °C is crucial. In this study, our objective is to investigate the effects of the promoters MnOx and FeOx on the stability of the Co3O4 phase supported on CeO2 and CO-PROX activity. Monodispersed Co3O4 nanoparticles were synthesized via a surfactant-free non-aqueous thermal method. 10 wt.% Co3O4 was supported and promoted via wet impregnation using ultrasonication. The addition of the promoters improves the redox properties of Co3O4. TPR showed an increase in the reduction temperature of Co3O4, while TPO showed a decrease in the re-oxidation temperature of metallic Co. Additionally, COTPRE showed that the promoted catalysts have a higher oxygen storage capacity when compared to the unpromoted catalyst. Catalytic performance evaluation was performed in a fixed bed reactor in the feed gas 1 % CO, 1 % O2, 47 % H2, and 51 % N2 from 50 to 450 °C. The onset temperature for CO methanation on Co3O4/CeO2 was 275 °C and the highest CO conversion achieved was 70% at 220 °C. The addition of 0.3 wt.% MnOx does not change the onset temperature for CO methanation. However, CO conversion increased to 84 % between 240-260 °C. An increase in the MnOx content to 0.5 wt.% increases the onset temperature for CO methanation to 300 °C and the highest CO conversion achieved was 98 % from 200-240 °C. A further increase in MnOx to 1 wt.% increases the CO methanation onset temperature to 310 °C, however, the CO conversion decreases to 92 % from 180-200 °C. The decrease in the optimum temperature for the 0.5 wt.% MnOx promoted catalysts might be beneficial Addition of 0.3 wt.% FeOx increases the onset temperature for CO methanation when compared to the unpromoted catalyst to 300 °C. Furthermore, CO conversion increased to 84% between 240-260 °C. An increase in the FeOx content to 0.5 wt.% does not change the onset temperature for CO methanation but the highest CO conversion achieved was 100 % from 210-220 °C. A further increase in FeOx to 1 wt.% increases the CO methanation onset temperature to 310 °C, however, the CO conversion decreases to 88 % from 220-230 °C.